Implementing Exchange Formation Activity to Improve Students’ Speaking Ability - Caltira Rosiana (STKIP PGRI Nganjuk, 2017)
The goal of English English teaching especially especially speaking skill in the classroom is to stimulatestudents to express their ideas in the target language. Since the most important thing in speaking skill is how to make the listener understands the speaker‟s message, Exchange Formation Activity can be used to improve students‟ speaking ability. This is because this method can be applied for teaching speakingeffectivelyin several ways. In teaching speaking, lecturers who teach English should make sure that the instructionsof the speaking material are related to the students‟ real life environment. Thus, the students can connect their speaking practice toexperiences in their daily activities.Thisstudy focused on the leacturer‟s teaching process(English class management and teaching method) and employed CAR research design.Thedata for this study are acquired from evaluation and observation. There were several evaluations included; they werepre-test, treatment on cycle I and II, and post-test. The aim of the activities was to know whether the students improved their learning or their learning became less effective afer treatment. The results showed thatthe average score for students‟ pre-test was 66.5. The result of the first treatment was 62, the second treatment was 85, and the post test was 88. The students‟post test‟smean score was 88. In conclusion after being treated using Exchange Formation Activity,thestudents‟ speaking abilitywassuccessfully improved which was shown by the final mean score 88 in the post test.